2010
DOI: 10.2527/jas.2009-2313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplemental vitamin A concentration on performance, carcass merit, serum metabolites, and lipogenic enzyme activity in yearling beef steers123

Abstract: A randomized complete block design experiment with 360 single-source black yearling steers (average BW = 316.1 +/- 9.1 kg) fed a 91% concentrate (steam-flaked corn base) diet was conducted to evaluate the effects of supplemental vitamin A (0, 1,103, 2,205, 4,410, or 8,820 IU/kg of dietary DM) on plasma and liver vitamin A and E concentrations, lipogenic enzyme activity, marbling score, and performance of yearling steers. Final BW (586, 580, 590, 585, and 584 kg for 0, 1,103, 2,205, 4,410, and 8,820 IU of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
20
0
2
Order By: Relevance
“…Therefore, reducing vitamin A intake has been used to enhance intramuscular lipid accumulation and marbling in finishing beef cattle (Arnett et al, 2009; Gorocica-Buenfil, Fluharty, Bohn, Schwartz, & Loerch, 2007; Pickworth, Loerch, & Fluharty, 2012a, 2012b; Smith et al, 2009; Ward, McKinnon, Hendrick, & Buchanan, 2012). However, there are also reports showing that vitamin A deficiency has no effect on lipid metabolism and marbling (Bryant et al, 2010; Gorocica-Buenfil, Fluharty, Bohn, et al, 2007; Gorocica-Buenfil, Fluharty, & Loerch, 2008; Gorocica-Buenfil, Fluharty, Reynolds, & Loerch, 2007; Pickworth et al, 2012a, 2012b). Such discrepancy could be due to the difference in the degree of deficiency, time and duration of deficiency, as well as cattle nutrition and genetics.…”
Section: Retinoic Acid and Lipid Accumulation In Mature Adipocytesmentioning
confidence: 99%
“…Therefore, reducing vitamin A intake has been used to enhance intramuscular lipid accumulation and marbling in finishing beef cattle (Arnett et al, 2009; Gorocica-Buenfil, Fluharty, Bohn, Schwartz, & Loerch, 2007; Pickworth, Loerch, & Fluharty, 2012a, 2012b; Smith et al, 2009; Ward, McKinnon, Hendrick, & Buchanan, 2012). However, there are also reports showing that vitamin A deficiency has no effect on lipid metabolism and marbling (Bryant et al, 2010; Gorocica-Buenfil, Fluharty, Bohn, et al, 2007; Gorocica-Buenfil, Fluharty, & Loerch, 2008; Gorocica-Buenfil, Fluharty, Reynolds, & Loerch, 2007; Pickworth et al, 2012a, 2012b). Such discrepancy could be due to the difference in the degree of deficiency, time and duration of deficiency, as well as cattle nutrition and genetics.…”
Section: Retinoic Acid and Lipid Accumulation In Mature Adipocytesmentioning
confidence: 99%
“…The HCW was also significantly affected by vitamin A treatment (P < 0.001) again with the steers on the 25% level having the heaviest carcass. Previous research has not found an association between restricted vitamin A levels in beef cattle diets with performance parameters such as ADG or final finishing weight (Gorocica-Buenfil et al, 2008;Pickworth et al, 2009;Bryant et al, 2010). There was no main effect of vitamin A treatment on marbling score of the LT muscle.…”
Section: Resultsmentioning
confidence: 57%
“…However, other studies have not shown any clear relationship between supplemental VA and the marbling score (Bryant et al . ). It should be noted that Japanese Black cattle are unique in their significant genetic potential for marbling (Bryant et al .…”
Section: Introductionmentioning
confidence: 97%